The development of an index of rural deprivation: A case study of Norfolk, England. (April 2019) - Burke, Amanda; Jones, Andy
Abstract: Geographical deprivation indices such as the English Index of Multiple Deprivation (IMD) have been widely used in healthcare research and planning since the mid-1980s. However, such indices normally provide a measure of disadvantage for the whole population and can be inflexible to adaptation for specific geographies or purposes. This can be an issue, as the measurement of deprivation is subjective and situationally relative, and the type of deprivation experienced within rural areas may differ from that experienced by urban residents. The objective of this study was to develop a Rural Deprivation Index (RDI) using the English county of Norfolk as a case study, but with a view to adopting a flexible approach that could be used elsewhere. It is argued that the model developed in this research gives clarity to the process of populating an index and weighting it for a specific purpose such as rural deprivation. This is achieved by 'bundling' highly correlated indicators that are applicable to both urban and rural deprivation into one domain, and creating a separate domain for indicators relevant to the setting of interest, in this case rural areas. A further domain is proposed to account for population differences in rural areas. Finally, a method was developed to measure variability in deprivation within small areas. The RDI results in more rural areas in Norfolk falling in the most deprived quintile, particularly those classified as 'Rural town and fringe in sparse settings'; these areas also have high levels of heterogeneity of deprivation when using the variability measure created. This model proposed has the potential to provide a starting point for those who wish to create a summary deprivation measure taking into account rurality, or other local geographic factors, and as part of a range of approaches that can be used to allocate, or apply for, resources. Highlights: National indices of deprivation typically poorly represent rural disadvantage. Paper presents new method to better depict deprivation in rural settings. Depicts granularity of rural disadvantage better than English deprivation index. Resulting index valuable for rural health and social service planning.